Synthesis and Characterization of a New Azo Ligand Derivative from 4,5-BIS(4-Methoxyphenyl) Imidazol and its Metal Complexes and Biological Activity Study of its PD(II) Complex - Fatema Jabbar Ali, Esraa Rasool Radhi, Khdeeja Jabbar Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
In the current work, the azo ligand and its Pd (Ⅱ), Cd (Ⅱ), Zn (Ⅱ) and Hg (Ⅱ) complexes were synthesized, characterized and their spectroscopic characteristics were studied. The new ligand was synthesized from the coupling reaction between 4,5-bis(4-methoxy phenyl)imidazole and the diazonium salt of 4-Amino benzoic acid in an alkaline medium at 0-5 ᵒC. the new azo metal complexes were prepared by the reaction between the ligand and metals chlorides. All the synthesized compounds were characterized by FT-IR, 1H-NMR, Mass spectral analysis, UV-Vis spectrophotometric, molar conductivity, and magnetic sensitivity. The biological activity of the azo ligand and its Pd (Ⅱ) complex was also studied. keywords: Azo compound, 4,5-di (4-methoxy phenyl) imidazole, azo metal complexes